Impacto do sistema de autotransfusão no uso de hemocomponentes em cirurgias de revascularização do miocárdio - Silva, Leonardo Leiria de Moura da (2013)
The administration of blood products is someway potential in patients undergoing cardiac surgery, due to higher morbidity in this population and the complexity inherent in the procedure itself. Coronary artery bypass grafting (CABG) is the most performed cardiovascular surgery, often associated with cardiopulmonary bypass (CPB). CPB is related to greater need of blood transfusion in such surgery, however different techniques can be applied in order to reduce this need. It is well established that the miniaturization of the CPB circuit (miniCPB) correlates with lower intraoperative blood loss and less requirement of blood transfusions. Cell saver autologous blood transfusion system reuses red blood cells lost in intraoperative bleeding, through a mechanism of aspiration, filtration, washing and concentration, with subsequent reinfusion to the patient. This system adds security to perioperative transfusion process, exceedingly reducing the requirement of pRBC in cardiovascular surgeries. The main objective of this dissertation was to evaluate the impact of cell saver autologous blood transfusion system on the use of blood products in coronary artery bypass grafting surgery. We carried out a cross-sectional study in 87 patients undergoing primary elective CABG with miniCPB, divided in two groups 44 without-CSS and 43 with-CSS. All data were retrieved from medical records. We investigated the necessity of absolute use and the volume of blood components in this population, as well as cardiovascular risk factors and pre and intraoperative surgical parameters. There was no significant difference between the two groups in terms of cardiovascular risk factors and pre and intraoperative variables, with significance level taken as 5%. When we evaluated the absolute use of pRBC during surgery, there was a statistically significant difference (p=0.00008) between groups without-CSS (21/44 cases 47.7%) and with-CSS (4/43 cases 9.3%). There was also a strong statistically significant difference (p=0.000117) in the volumes of pRBC between without-CSS (198.65±258.65ml) and with-CSS (35.06±125.67ml) groups. On the other hand, in the early postoperative period (up to 24h) there was no difference regarding the absolute use or the volumes of pRBC between both studied groups. The use of a cell saver autologous blood transfusion system results can reduce the requirement of erythrocyte transfusion (pRBC) in coronary artery bypass grafting surgery associated to miniCPB.